MAQASID SHARIA AND ISLAMIC BANK PERFORMANCE: A SYSTEMATIC REVIEW - Syarifah, Lailatis; Muhfiatun, Muhfiatun; Fitrijanti, Tettet; Prasojo, Prasojo (I-Economics, 2021)
Maqasid sharia contains elements of maintaining faith, guarding oneself, maintaining reason, maintaining bloodlines and safeguarding property. Until now, the maqasid of sharia is considered to be the most ideal as a measure of the performance of sharia banking with the dimension of maqasid sharia with the aim of Islamizing banking. Islamic banking as a business entity that aims to make a profit but must also comply with Islamic law and provide benefits in the social sector through the distribution of zakat, infaq, alms, csr, and qardul hasan loans. This study is a literature review study on the relationship between Islamic maqasid and Islamic banking performance measurement. This study contains the philosophy, terminology of sharia maqasid, and research results relating it to the performance of Islamic banking. The conclusion from the literature review is that Islamic maqasid can be adopted as a measure of the performance of Islamic banking. Many empirical studies have examined the use of maqasid sharia as an indicator, but there is no consistency. Therefore, Islamic banking regulators need to prepare instruments and guidelines so that these measurements can be adopted easily and uniformly.